Evaluation of the effect of different radiation approaches on the estimation of evapotranspiration using the FAO Penman-Monteith model - Orozco Medina, Ismael; Alvarado Barrientos, Maria Susana; López de la Cruz, Jesús; Ramírez Orozco, Aldo Iván (Acta Universitaria, 2019)
Evapotranspiration is a very important process in the correct calculation of water availability, but it is one of the most difficult to estimate the hydrological cycle in regions with limited meteorological information. An alternative recently used to solve this problem is the use of satellite products with evapotranspiration at a regional scale. However, these products must be validated with information observed for their regional application, but the information is difficult to obtain in tropical latitudes. To solve this, an improvement to the FAO Penman-Monteith equation is proposed by including the spatial and temporal variability of the net radiation (Rn) with the Viewshed algorithm. The results show an improvement of 1.1% when comparing the results of the reference evapotranspiration against the estimates coming from the satellite product MOD16A3 and using the traditional calculation form of Rn.